The Complexity of Texts Read by Grades 3 to 6 English Learners in Muscat Governorate in Oman - Al-Mamary, Fakhrah (2020)
The key to success in reading texts lies in their careful design with progressing levels of complexity that are within the reader’s competence. The selection of these texts that hold the right level of complexity is more critical in initial reading phases because it is during these phases that the stage is set for later reading development. Therefore, understanding the factors that contribute to the complexity of texts in a specific context aids towards establishing a text complexity model. Hence, the current thesis attempts towards developing a new model for the concept of Text Complexity for texts that are read by young EFL learners. The model is the result of the exploration of the factors that affect text complexity and which are related to texts, to readers or to the interplay between texts and readers while reading. The exploration of these factors is grounded on the Interactive View of Reading by Rumelhart (1985) while also attending to other theories and models that indirectly tackle factors related to readers and texts. The factors have been explored using a mixed –methods- approach since conducting text complexity research using quantitative tools only or qualitative tools only holds both strengths and limitations. Hence, under Pragmatism, the researcher was able to conduct the current research within both the positivist and the interpretivist paradigms. The data collection tools included readability formula (Lexile), qualitative judgments of texts, a reading fluency test (WCPM), miscue analysis and interviews. The research was conducted in three government schools in Muscat and it included 32 young learners from grades three, four, five and six. Seventy texts were analyzed quantitatively by Lexile and fifty texts were analyzed qualitatively by twenty educational professionals. The Statistical Package for the Social Sciences (SPSS) was used to analyze the quantitative data generated from the different research tools. The findings of this research suggest that text complexity is influenced by the text factors, reader factors and factors resulting from the interplay between texts and readers during reading. The text factors include the unsystematic progression, the texts’ linguistic complexity, the limited focus on learning- to –read skills, the books’ layout, and the books’ content. The reader factors include reader’s prior knowledge, the reader’s reading strategies and the reader’s interest. The reader- text factors involve the inadequate level of reading fluency, the inability of readers to select books that match their level and the lack of adequate English language proficiency. The findings of this research have several implications towards a renewed model of text complexity for EFL learners. The findings have also several implications on the policies of authoring, evaluating and selecting texts for young learners of English in Oman in addition to its theoretical and methodological contributions to the research of text complexity in an EFL setting.